SELF ESTEEM IN MEDELEINE L’ENGLE’S A WRINKLE IN TIME - Aillen Robiatul Adawiyah (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
This study aims to analyze the process of achieving human needs by Meg Murry and its influencing factors. Abraham H. Maslow's hierarchy of human needs is the main theoretical basis for this research. This research uses textual information in the novel as a basis, which makes this research a descriptive qualitative study. The main data in this study are A Wrinkle in Time by Madeleine L'Engle and journal articles as supporting material. The research was conducted by analyzing the process to get the peak of human needs with the hierarchy theory of human needs and the supporting factors. This research focuses on the time travel of Meg, Charles, and Calvin to save Meg and Charles' father who are trapped in a parallel world. The result of this research is that Meg has succeeded in fulfilling the self esteem needs with the help of family, friends, and the right environment. Meg also realizes that the flaws she has are not always an obstacle to loving herself.